The Level of the Organizational Climate in Iraqi Olympic Sports Federations - Hussein, Luay (Journal of Physical Education, 2016)
The problem of the study can be summed up in this question: What is the level of the organizational climate in Iraqi Olympic Sports Federations? The study aimed at identifying the dominant organizational climate in Olympic sports federations. The researcher has used the descriptive method conveniently. She also adopted an organizational climate measure to achieve the aims of the study. The subjects of the study therefore included members of the administrative body in the Iraqi Olympic Federations totaled (181) members in (22) Olympic Federations rating (100%) of the population of the study. Conducting the statistical treatment to the measure, the researcher found out a highly opened organizational climate in the views of the members of the administrative body of the Iraqi Olympic sports federations. In light of the conclusions, the researcher recommends the guardian of the Iraqi Olympic Sports Federation to identify a number of standards and technical foundations for the selection of the administrative bodies that can bring about change, creativity and innovation with high efficiency.